Process Types in Mechanical Engineering Texts: Transitivity Analysis - Mulyati Khorina (Linguistics and ELT Journal, 2020)
This paper reports the study of Mechanical Engineering texts which is concerned with Transitivity system. The study aims to investigate the process types that frequently occur in this kind of texts and find out the process type that dominated the texts. Hence, to analyze the qualitative data obtained from an introductory textbook of Mechanical Engineering, a Systemic Functional Linguistics framework was applied. The results show that only three types of process were identified: Material, Relational, and Existential. Among these process types, the Relational process appears to be dominant. These findings may implicate teaching ESP, primarily teaching English for Mechanical Engineering students.